Affects and emotions in upbringing and education - Žalec, Bojan (Šolsko polje, 2012)
The article is divided to three parts. In the first part, the author argues for the importance of body and bodily relations. On this basis, he argues for the importance of living inter-bodily relations between a student and a teacher. Successful distant education is not possible. In the second part, the author deals with the problems of the modern youth and pupils. He argues for the importance of self-consciousness, identity, recognition and confirmation for the success and good life of young people. Their identity is built up through the relationships with their parents and teachers (significant others). The author points to the fact of the increasing emotional illiteracy of the youth in Europe and the necessity of emotional upbringing. Parents and teachers play the crucial role in it. Alas such upbringing is too often almost totally absent and this leads to indiff erence, apathy, violent acts and other negative phenomena by our youth. Th e crucial factor in the development of such phenomena is bad or empty communication between children or students on one hand and adults, parents or teachers on the other. In the third part, the investigations are based on the findings of the (modern) theory of affects. The author argues for the importance of body, affectivity, and of teacher for school and education. Th e conclusion entails a short outline and recommendation of the personalist pedagogy.
Keywords: body; učitelji; učenci; bodily relations; identiteta; teachers; samozaupanje; students; identity; medosebna komunikacija; self-consciousness; čustva; afekti; recognition; communication; vzgoja in izobraževanje; emotions; pedagogika; affects; upbringing; education; pedagogy